Co‐Production of Bio‐Ethanol and Bio‐Oil from Different Species of Macroalgae. Issue 9 (4th March 2021) - Li, Chen; Liu, Zhongxin; Ning, Dandan; Pan, Jingwen; Li, Jinhua
Abstract: This paper proposed a methodology to realize the co‐production of bio‐ethanol and bio‐oil from macroalgae. Bio‐ethanol were obtained from three different species of macroalgae ( Enteromorpha prolifera, Undaria pinnatifida and Gelidium amansii ) by hydrolysis and fermentation. And then the residues after hydrolysis were converted into bio‐oil with high heating value via deoxy‐liquefaction. The yield of reducing sugar and bio‐ethanol from three macroalgae were calculated. The red algae (Gelidium amansii) produced the reducing sugar with largest yield of 320±4.1 mg/g and ethanol with a maximum content of 9.09±0.07 g/L. Besides, the properties and components of the liquid oils have been analyzed and compared with each other. The lower oxygen content (4.47 %, 4.98 % and 4.02 %) and higher heating value (45.06, 44.53 and 45.12 MJ/kg) of the liquid oils were detected respectively. The results indicated that macroalgae had a great potential for co‐production of bio‐ethanol and high‐quality bio‐oil. Abstract : Three different species of macroalgae ( Enteromorpha prolifera, Undaria pinnatifida and Gelidium amansii ) were enzymatically hydrolyzed and then filtrated. The sugar solution was fermented to produce bio‐ethanol. Furtherly, the solid residues after hydrolysis were converted into bio‐oil via deoxy‐liquefaction. The yield of bio‐ethanol and the compositions of the bio‐oil were analyzed and compared with each other.